Enrichment of a fruit-based beverage in dietary fiber using basil seed: Effect of Carboxymethyl cellulose and Gum Tragacanth on stability. (December 2016) - Hajmohammadi, Azam; Pirouzifard, MirKhalil; Shahedi, Mohammad; Alizadeh, Mohammad
Abstract: Due to the importance of dietary fiber intake on health, in this study, the production of fruit based beverages containing basil seeds, as a dietary fiber source, was evaluated. Basil seeds were evaluated for nutrients and were used in beverages at three levels (10, 30 and 50: 100 (Wswell basil seed /Wfruit based beverage )). Also Gum Tragacanth (GT) and Carboxymethylcellulose (CMC) were added to these samples, separately, for the suspension of the seeds. The beverages were examined over a period of 60 days, at 4 °C, by evaluating color factors (L*, a*, b*), zeta potential (Z), rheological and organoleptic properties etc. Results showed that basil seeds have a high ratio of protein and fiber, and their addition to beverage led to increase in absolute Z, but the taste satisfaction and color factors decreased. Also addition of both hydrocolloids, led to the increase of absolute Z and the development of pseudo-plastic behavior in the beverages. Samples stability and appearance improved with increasing concentrations of hydrocolloids but an increase of more than 0.25%, caused reduction in mouthfeel satisfaction. Results indicated that using basil seeds with the addition of 0.25% GT, led to the production of enriched beverage with suitable stability. Highlights: Using basil seed led to increase of nutrients especially dietary fiber. The k factor of GT and CMC were similar but the absolute Z of CMC was higher. GT was more effective than CMC in terms of beverage stability and seed suspension. Increase in gum concentration, over 0.25%, had a negative effect on mouth feel. Increase in GT concentration and seed ratio led to darkening of samples.